Correction: Hunting and consumption of rodents by children in the Lassa fever endemic area of Faranah, Guinea. - Moussa Douno; Emmanuel Asampong; N'Faly Magassouba; Elisabeth Fichet-Calvet; Almudena Marí Sáez (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0009212.].